EVALUATION OF BLOOD SAMPLING TIMES AND INDICATIONS FOR THERAPEUTIC DRUG MONITORING SERVICES - AISHAH HAMZAH; AISHAH HAMZAH; AB FATAH AB RAHMAN; AB FATAH AB RAHMAN; AISHAH HAMZAH; AB FATAH AB RAHMAN (Universiti Sains Malaysia, 2008)
The appropriateness of sampling times and indications for monitoring of serum drug concentrations for the purpose of therapeutic drug monitoring (TDM) were evaluated at three hospitals on the east coast of Malaysia. Appropriateness criteria for indication and sampling were adapted from previously published criteria and with input from local TDM pharmacists. Six drugs were chosen, namely gentamicin, digoxin, carbamazepine, phenobarbital, phenytoin, and valproic acid. A total of 265 TDM requests were evaluated. Appropriateness of the indication for TDM ranged from 77.4% to 82%, while that for sampling ranged from 34.2% to 62.1%. There were no significant differences between the three hospitals in both categories of appropriateness. Among different drug groups, the percentage of appropriate indication was found to be highest with antiepileptic drugs. Antiepileptic drugs, however, had the lowest rate of appropriate sampling. Overall, findings from the three hospitals showed very encouraging results with almost 80% of the requests considered as appropriately indicated. However, the percentage of appropriateness of sampling was lower, and thus may require further investigation.